PENGARUH DESENTRALISASI FISKAL, AKUNTABILITAS, DAN SISTEM PEMERINTAHAN BERBASIS ELEKTRONIK (SPBE) TERHADAP INDIKASI KORUPSI DI PEMERINTAH DAERAH (Studi Empiris Kabupaten/Kota di Provinsi Jawa Timur Tahun 2019-2022) - Anggono, Galuh Try; Haryanto, Haryanto (Diponegoro Journal of Accounting, 2024)
This study aims to determine the effect of fiscal decentralization, accountability, and e-government on indications of corruption in local governments, with a focus on districts and cities in East Java Province in 2019–2022. The main objective of this study is to evaluate how these variables affect corruption indications and provide empirical evidence for policy and governance improvements.This research uses a quantitative approach with panel data regression analysis. The independent variables in this study include fiscal decentralization, audit opinion, performance accountability, and e-government. Control variables such as the Human Development Index (HDI) and personnel expenditure are also considered. Data was collected from various official reports and analyzed using EViews 13 software.The results showed that fiscal decentralization and performance accountability have a positive but statistically insignificant effect on corruption indications, while audit opinion and e-government systems have a negative and significant effect. The adjusted R-squared value of 0,3977 indicates that about 39,77% of the variation in corruption indications can be explained by the independent variables and control variables in this model, which indicates that other factors not studied can also contribute to the level of corruption.